2021
DOI: 10.3390/agronomy11050906
|View full text |Cite
|
Sign up to set email alerts
|

Soil Enzymatic Activities and Microbial Community Structure in Soils Polluted with Tetracycline Antibiotics

Abstract: A laboratory experiment was performed to examine the medium-term influence of three tetracycline antibiotics (chlortetracycline, CTC; tetracycline, TC and oxytetracycline, OTC) at different concentrations in four agricultural soils with similar pH and different soil organic content. After a 42-days incubation period, three different soil enzymes (β-glucosidase, urease, and phosphomonoesterase) were estimated, as well as the phospholipid fatty acids (PLFAs). A residual effect was observed on all microbial param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…The sensitivity of dehydrogenases and catalase to tetracycline was relatively low. This is consistent with sparse and inexplicit reports related to the effect of this group of antibiotics on the activity of soil enzymes [ 85 , 95 ]. Wei et al [ 72 ] and Kessler et al [ 95 ] emphasized that soil contamination with Tc impaired the enzymatic activity of soil, particularly in the case of dehydrogenases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The sensitivity of dehydrogenases and catalase to tetracycline was relatively low. This is consistent with sparse and inexplicit reports related to the effect of this group of antibiotics on the activity of soil enzymes [ 85 , 95 ]. Wei et al [ 72 ] and Kessler et al [ 95 ] emphasized that soil contamination with Tc impaired the enzymatic activity of soil, particularly in the case of dehydrogenases.…”
Section: Discussionsupporting
confidence: 92%
“…The increased OTU numbers of bacteria from the following genera: Cellulosimicrobium , Nocardioides , Candidatus Solibacter , Streptomyces , Terracoccus , Arthrobacter , Phycicoccus , Kutzneria , and Amycolatopsis belonging to the phylum Actinobacteria and bacteria from the genera: Rhodoplanes , Burkholderia , and Rhodanobacter belonging to the phylum Proteobacteria in the soils contaminated with Tc can be associated with a growing ability of these microorganisms to degrade this antibiotic [ 54 , 83 ] and use it as a source of carbon and energy [ 24 , 58 ]. Potentially, the adverse Tc effect on the bacteria from the phylum Proteobacteria represented by Kaistobacter , Sphingomonas , Sphingobium , Luteibacter , and Steroidobacter genera could have been masked by enhanced activities of other microorganisms capable of developing in the presence of Tc, probably, by using compounds released from lysed cells of microorganisms [ 58 , 79 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The review clearly evidences that the response of microorganisms to the presence of these compounds measured by means of different parameters related to their mass, activity, and diversity (microbial C, total PLFA biomass and specific microbial groups PLFA biomass, soil respiration, bacterial growth, soil enzymes, microbial community structure), were variable; thus, although a negative temporal effect was often observed on microorganisms living in the soil, non effect, or even a positive effect, could also be detected. This is in agreement with recent investigations conducted by our research group performed with acid agricultural soils located in Galicia (NW Iberian Peninsula) added with antibiotics of different groups (tetracyclines, sulfonamides, fluorquinones, penicillins, cephalosphorine, diaminopyridine, β-lactams) (Santás-Miguel et al, 2020a;Santás-Miguel et al, 2020b;Santás-Miguel et al, 2020c;Rodríguez-González et al, 2021;Santás-Miguel et al, 2021;Rodríguez-González et al, 2022;Santás-Miguel et al, 2022;Rodríguez-González et al, 2023).…”
Section: Introductionsupporting
confidence: 92%
“…This is consistent with numerous field and laboratory studies concerning phospholipid fatty acid profiles performed with different soils following the impact of numerous stress agents (e.g., wildfire, prescribed fire, soil heating, fire retardants, post-fire rehabilitation treatments, vegetation type, soil management, climatic conditions, herbicide application, heavy metal pollution) which found that microbial communities of the same soil with different disturbances were grouped together and separated from microbial communities of other soils (Bossio et al, 1998;Díaz-Raviña et al, 2006, 2018Fernández-Calviño et al, 2010;Mahía et al, 2011;Barreiro et al, 2015;Lombao et al, 2015). Likewise, a similar medium-term response of microbial communities was observed following the addition of antibiotics of both veterinary use such as tetracyclines (Santás-Miguel et al, 2021) and human use such as ciprofloxacin, trimethoprim, and amoxicillin (Rodríguez-González et al, 2022) to some soils of the same temperate humid zone.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation